Exploring The Factors Affecting On Reproductive Health Of Adolescents In Rural Areas - Achmad Ali Basri; Nurul Maurida; Irwina Angelia Silvanasari; Trisna Vitaliati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
The understanding of Indonesian teenagers, especially in rural areas, about reproductive health is still very low, especially among teenage girls, only 10.4% of the 15-24 year old age group know about reproductive health, resulting in various reproductive health problems such as free sex, sexual harassment, dropping out of school, early marriage, pregnancy outside of marriage, and many religious marriages. The purpose of this study was to explore the description of factors affecting on reproductive health management in adolescents. The study used a qualitative method with a phenomenological approach. Participants were selected using a purposive sampling strategy. There were 12 participants with the criteria, namely adolescents aged 14-18 years, receiving data collected through in-depth interviews, observation, and documentation. The results of the research theme were obtained using collaizi analysis which was arranged in stages using data triangulation starting from coding, categorization, and theme formation. Based on the results of the analysis of participant information, three main themes were formulated, namely knowledge, parental support, and peers. The conclusion of this study is that factors that influence adolescent reproductive health in rural areas are knowledge factors, family support and peer support. Adolescents are expected to be able to take responsibility for maintaining their reproductive health independently, increase spirituality and be able to maintain open communication with their parents and peers.